Can Japanese Learners Pass the JLPT N3 by Reading A3! Visual Novel? - Aida, Nurul Zia; Putri, Renindra Atsilah; Putri, Amalia; Arrahmah, Tazkia Syifa; Kusrini, Dewi (Chi'e: Journal of Japanese Learning and Teaching, 2021)
A visual novel is a reading media in the form of conversations between characters shown in a static anime style that attracts readers to continue reading it. Equipped with audio in Japanese and translation in English, it is estimated that visual novels can be used as an exciting learning media for students. This study aims to determine the possibility of visual novels, which are usually used as a game for entertainment purposes, as a medium for learning Japanese to pass the JLPT (Japanese Language Proficiency Test). The method used in this stusdy is a quantitative method to find the matching vocabularies, with a listening and note-taking method for data collection. The data analyzed here is a conversation transcript of some chapters of A3! visual novel and JLPT 2018 questions ranging from N5 to N3 level. The A3! visual novel data are grouped according to the JLPT's four linguistic aspects: Moji goi, bunpou, dokkai, and choukai, at each level (N5 to N3). The analysis results show that the visual novel A3! can be used as a strengthening medium for students to pass the JLPT from N5 to N3.